2020
DOI: 10.1002/jat.4059
|View full text |Cite
|
Sign up to set email alerts
|

Aconitine disrupts serotonin neurotransmission via 5‐hydroxytryptamine receptor in zebrafish embryo

Abstract: Medicinal plants of the genus Aconitum are one of the most commonly used herbs in traditional medicine in East Asia to treat conditions related to the heart, pain, or inflammation. However, these herbs are also dangerous as accidental poisoning due to misuse is a recurring issue. These plants contain a number of diester‐diterpenoid alkaloid compounds and aconitine is the most abundant and active one. This study investigated neurotoxicity of aconitine to zebrafish embryos in early development in relation to ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…In the present studies, aconitine-induced neurotoxicity possibly involves disturbance of ion homeostasis, induction of oxidative stress and apoptosis, mitochondrion injury, interference with energy metabolism, and alteration of neurotransmitter levels (Yamanaka et al, 2002;Peng et al, 2009;Zhao et al, 2010;Chen et al, 2021;Liang Yang et al, 2021). The typical clinical features of aconitine poisoning involved involuntary tremors and progressive dyskinesia (Pan and Peng, 2017).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present studies, aconitine-induced neurotoxicity possibly involves disturbance of ion homeostasis, induction of oxidative stress and apoptosis, mitochondrion injury, interference with energy metabolism, and alteration of neurotransmitter levels (Yamanaka et al, 2002;Peng et al, 2009;Zhao et al, 2010;Chen et al, 2021;Liang Yang et al, 2021). The typical clinical features of aconitine poisoning involved involuntary tremors and progressive dyskinesia (Pan and Peng, 2017).…”
Section: Introductionmentioning
confidence: 64%
“…Although the brain tissue of zebrafish is simple, their embryos develop rapidly and the nervous system has matured on 5 days postfertilization (dpf) (Schweitzer and Driever, 2009). Overall, zebrafish has emerged as a promising and ideal model to investigate the mechanisms of druginduced neurotoxicity (Chen et al, 2021). In this study, we employed zebrafish larvaes and SH-SY5Y cells to quantify the effects of aconitine on morphology, neurobehavior and cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al reported that aconitine disrupts serotonin neurotransmission via the 5-hydroxytryptamine receptor and increases the frequency of coiling behavior in a dose-dependent manner. [65] Furthermore, it has been reported that aconitine induces developmental toxicity through ROS-mediated mitochondrial apoptosis involving the Nrf2/HO-1 and JNK/Erk pathways. [66] Different from the developmental toxicity mechanisms, our study suggested A. carmichaelii induces the neurotoxicity mechanism through excessive ROS involving Nox5 and DJ-1.…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al. reported that aconitine disrupts serotonin neurotransmission via the 5‐hydroxytryptamine receptor and increases the frequency of coiling behavior in a dose‐dependent manner [65] . Furthermore, it has been reported that aconitine induces developmental toxicity through ROS‐mediated mitochondrial apoptosis involving the Nrf2/HO‐1 and JNK/Erk pathways [66] .…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish embryos were exposed to three isomers of borneol from 4 hpf and were fixed by 4% paraformaldehyde overnight when the embryos developed to 72 hpf. The basic method of antibody staining is similar to our previous description (Chen et al, 2021). Zebrafish larvae sections were treated with proteinase K (Gibco, Carlsbad, USA) and rinsed with PBST (1× PBS containing 0.1% Tween20).…”
Section: Methodsmentioning
confidence: 99%